Shifting : how school leaders can create a culture of change - Richert, Kirsten; Ikler, Jeff; Zacchei, Margaret (Corwin Press, 2020)
Establish a school change culture where desired outcomes are actually achieved Change in schools is hard, but often essential. Are you prepared to lead colleagues through the shifts required by unprecedented, complex change? Shifting offers an integrated tapestry of wisdom and support for educational changemakers intent on meaningful collaboration in a positive, engaged workplace. Change leaders learn to shift the emphasis in the change process from procedure to the people implementing change ; Move from an environment of "command and control" to one of leaders creating other leaders ; Reframe change as an essential shift in school culture rather than a series of episodic events.